Penguatan Kompetensi Guru Biologi Sidoarjo Menghasilkan Buku Ajar Bebas Plagiarisme - Iman Pasu Marganda Hadiarto Purba; Hebert Adrianto; Hanna Tabita Hasianna Silitonga (Labor Jurusan Sosiologi, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2020)
Making textbooks is an important strategy in increasing the productivity and effectiveness of the teaching and learning process in schools. Textbooks are not only a supplementary learning medium. Textbooks are a necessity and effective learning media to improve the quality of learning for students. However, making textbooks is inseparable from the challenges of plagiarism which can have legal consequences for textbook authors, in this case teachers. In the current digital era, easy access to information is a big challenge for teachers who write textbooks because the work that is produced is quickly finished but violates the ethics of writing the work. Therefore, specifically for teachers who join the Sidoarjo Subject Teacher Conference (MGMP), teachers are given strengthening competencies to produce textbooks that are free of plagiarism. The method of implementation is through training, namely by providing weighting on the legal aspects of plagiarism and mentoring using the online method. The method of assessment is carried out by pre-test and post-test, as well as strengthening the plagiarism material. All the participants felt tremendous benefits according to their testimonials because so far they have often ignored the rules regarding plagiarism. This Biology teacher will produce a Biology textbook that is free from plagiarism with new insights and skills from the teachers in doing citations or quotations.